Adolescence risk factors for meniscus and ligamentous knee injuries in adulthood: A longitudinal study - Vaajala, Matias; Teuho, Alisa; Liukkonen, Rasmus; Ponkilainen, Ville; Rimpelä, Arja; Koivusilta, Leena K.; Mattila, Ville M. (Wiley, 2025)
Purpose: Our aim is to investigate the inﬂuence of adolescent health‐related
behaviours on the occurrence of meniscus and ligament injuries in a large
cohort of Finnish adolescents with an average 27‐year follow‐up.
Methods: The baseline data were surveys conducted biannually from 1981 to
1997, and these were individually linked to outcomes, as well as meniscus and
ligamentous knee injuries obtained from the Care Register for Health Care. A
total of 47,747 participants were included. Of these, 22,020 were male and
25,727 were female. A Cox regression model was used to analyze the asso-
ciations between exposure variables in adolescence (physical activity in sports
clubs, other physical activity, overweight, smoking, monthly drunkenness, pres-
ence of chronic disease, family socioeconomic status) and the risk for knee
injuries. Adjusted hazard ratios (aHR) with 95% conﬁdence intervals (CIs) were
computed.
Results: The mean follow‐up time among the participants was 26.8 years
(standard deviation [SD]: 4.1 years). A total of 1163 (2.4%) persons suﬀered a
meniscus injury, and 1831 (3.8%) suﬀered a ligament injury. High physical
activity in sports clubs (aHR: 2.02, CI: 1.85–2.21), overweight (aHR: 1.37, CI:
1.12–1.68), monthly drunkenness (aHR: 1.37, CI: 1.19–1.57) and presence of
chronic disease (aHR 1.30, CI 1.08–1.56) increased the risk for meniscus inju-
ries. Similarly, high (aHR: 1.72, CI: 1.60–1.84) physical activity in sports clubs,
overweight (aHR: 1.26, CI 1.07–1.47), monthly drunkenness (aHR: 1.26, CI
1.13–1.41) and presence of chronic disease (aHR: 1.36, CI: 1.17–1.57)
increased the risk for ligament injuries.
Conclusions: Frequent physical activity in sports clubs presented a higher
risk for meniscus and knee ligament injuries in individuals under 40, com-
pared to degenerative factors such as being overweight or smoking. Inter-
ventions focusing on the suitable load level among adolescents with
frequent and high‐intensity physical activity, in addition to eﬀorts to reduce
negative habits should be prioritized to lower the knee injury risk.